Nutrition survey in elite rhythmic gymnasts - Cupisti, A.; D'Alessandro, C.; Castrogiovanni, S.; Barale, A.; Morelli, E. (The Journal of Sports Medicine and Physical Fitness, 2000)
Young female rhythmic gymnasts have been identified as a potential risk group for malnutrition because of their attitude of weight reduction and leanness. METHODS: This study aimed to assess the dietary practices of 20 rhythmic gymnasts of the Italian national team, on the basis of a three-day food records collected by clinical interview. Twenty-four age-matched non-athletic females served as controls. RESULTS: The reported energy intake was similar in gymnasts and controls (28.5+/-5.6 vs 28.2+/-7.8 kcal/kg b.w., per day), but less than the recommended and the estimated requirements. Energy intake from carbohydrates was higher (53+/-6 vs 49+/-6%, p<0.05) and that from lipids lower (31+/-6 vs 34+/-4%, p<0.05) in gymnasts than in controls. In the former the energy supply from breakfast was higher (24+/-2 vs 16+/-4%, p<0.001) and from snacks was lower (8+/-9 vs 17+/-10%, p<0.01). Gymnasts also distinguished from controls for lower cholesterol and saturated fatty acid intake, and for higher fibre (14+/-5 vs 9+/-2 g/1,000 kcal, p<0.001) and Vitamin A dietary content. Calcium, iron and zinc intake were less than 100% RDA in both groups. CONCLUSIONS: In some ways, dietary practices of rhythmic gymnasts meet nutritional recommendations more than those of non athletic controls, though discrepancy between reported energy intake and estimated energy requirement exists. Suboptimal calcium, iron and zinc intake were observed both in gymnasts and in controls, hence minerals supplementation could be required. The dietary attitude could be regarded as a positive aspect of rhythmic gymnastics, provided athletes, physicians and coaches correct dietary errors and avoid excessive food restrictions.